An Assessment of Leadership Styles and Emotional Intelligence Among Supervisors in Car Dealership: A Rank-and-File Employee Perspective - Angell Duque; Juliana Elizabeth Galang; Danielle Angela Jardin; Irvin Perono (Research Synergy Foundation, 2025)
Leadership plays an important role in shaping the dynamics in the workplace, including stakeholder performance and the overall success of the organization. Effective leadership alongside emotional intelligence can impact the productivity and motivation of an employee. This study assessed the different leadership styles – transactional, transformational, and charismatic and their relationship to emotional intelligence (awareness, empathy, social skills, and motivation). A total of 388 rank-and-file sales personnel in the automotive industry in the National Capital Region in Metro Manila, Philippines participated the survey. Quantitative research using simple random sampling was employed in the study. A self-made survey questionnaire was administered with a Cronbach's alpha of 0.87. The results revealed that the leadership styles and emotional intelligence were extensively exhibited by their immediate supervisor based on the assessment of the respondents. Furthermore, using regression analysis, data revealed that there is a significant relationship between empathy, social skills and motivation when transactional, transformational and charismatic types of leadership were considered. Awareness of the contrary resulted in a significant relationship with transformational and charismatic types of leadership, but not with to transactional types of leadership. This study makes a significant contribution to the understanding of how emotional intelligence influences leadership effectiveness in sales-driven industries. The results underscore the importance of incorporating emotional intelligence training into leadership development programs to foster stronger supervisor-employee relationships and enhance overall organizational performance.